2003
DOI: 10.1002/adfm.200390015
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Blue‐Luminescent Tris(8‐hydroxyquinoline)‐aluminum (Alq3)

Abstract: Using differential scanning calorimetry (DSC) measurements in combination with structural and optical characterization we have investigated the formation conditions of different phases of tris(8‐hydroxyquinoline)aluminum (Alq3). We have identified the δ‐phase as a high‐temperature phase of Alq3 being composed of the facial stereoisomer, and report an efficient method to obtain blue luminescent Alq3 by a simple annealing process. This allows the preparation of large amounts of pure δ‐Alq3 by choosing appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
175
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(206 citation statements)
references
References 12 publications
31
175
0
Order By: Relevance
“…To date, five crystalline phases ( , , , , and ) have been identified for Alq 3 [8][9][10]. To the best of our knowledge, -, -, and -Alq 3 are formed by meridional isomers, whileand -Alq 3 are formed by facial isomers [2,[5][6][7][10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…To date, five crystalline phases ( , , , , and ) have been identified for Alq 3 [8][9][10]. To the best of our knowledge, -, -, and -Alq 3 are formed by meridional isomers, whileand -Alq 3 are formed by facial isomers [2,[5][6][7][10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…The preparation and characterization of Alq 3 have been widely studied [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Because of the bidentate ligand, Alq 3 complexes form two isomers, as shown in Figure 1: meridional and facial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results seem to indicate that the amorphous phase in thin films is attributed to polymorphs composed only of mer-Alq 3 . Very recently, it has been reported that d-Alq 3 might be composed of fac isomers [7]. Therefore, there is now some disagreement about the amorphous structure based on the isomeric mixture of Alq 3 in thin films.…”
Section: Introductionmentioning
confidence: 99%
“…This arrangement in the solid state generates a significant overlap of the orbitals of the aromatic rings belonging to molecules situated in different planes. In Alq3 the conduction properties depend on the dominant type of stereoisomer, meridian or facial (Cölle, 2003), and are generated by the overlapping degree of the orbitals of the hydroxyquinoline ligands belonging to the neighbouring molecules.…”
Section: Electrical Conduction In Organic Molecular Compounds Heterosmentioning
confidence: 99%